PROCESS OF MAKING SUCKLING PIG AND FINANCIAL ANALYSIS WITH RAW MATERIALS BALI PIG (Case Study on Company Suckling Pig the Bali Pigs owned Made Sunaka) - P. K. P. N, Sastrawan; Budaarsa, K.; Mahardika, I G. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
283 This study aimed to to determine the process of making suckling pig made from raw bali pig and composition of spices. This research was conducted at the company of suckling pig made from raw the bali pig owned by Made Sunaka which is located in Banjar Pegending, Dalung Village, North Kuta District. The research conducted for 2 months that is from July until August 2016. The data used in this research is primary data which analyzed descriptively and financial analysis can be determined based on earnings analysis and R/C ratio. The research, the process of making suckling pig the bali pigs include the process of slaughtering, cleaning the epidermis skin, spawning the internal organs, piercing the pig with a rolling tool, tying the mouth and all four legs, filling the spice in pork belly and young water coconut. Next the pigs are lifted and placed on the pig's place with the pig's position beside the embers as they rotate the rolling tool. The color of pig bolsters from white to reddish brown looks soft pork bolsters are ripe. Suckling pigremoved from the next roll is done the packaging process. Spice ingredients used to make suckling pig made from raw bali pigis complete seasoning which consists of 18 types of spices ingredients typical of Bali. Seasoning ingredients consist of onion, garlic, turmeric, greater galingale, galangale, chili, ginger, pecan, nutmeg, ( Piper retrofactum ), pepper, lemongrass, coconut oil, A coroscalamus, coriander and salt. The value of shrinkage of pigs bali after becoming pig bolster is the greater the weight of pig bolsters the smaller the shrinkage. Financial analysis of the suckling pig bolsters business owned by Made Sunaka show the total cost for 2 months is Rp 88.249.553. Total revenue Rp 96.950.000, profit earned Rp 8.700.447 and R/C ratio that is 1.10. The results of financial analysis show that the effort of suckling pig owned by Made Sunaka is feasible to run.